2021
DOI: 10.1080/08941920.2021.1971808
|View full text |Cite
|
Sign up to set email alerts
|

The Gender Gap in Water Management Preferences: Analyzing the Influence of Environmental Concern and Political Knowledge

Abstract: To date, most studies on the role of women in water management have focused on local communities in developing countries, within which women are more vulnerable to hydrological risk. This study emphasizes the need to investigate the preferences of women in industrialized nations. The results of a representative opinion survey in Andalusia (Spain) reveal that, when it comes to water management, women tend to think primarily in domestic terms whereas men prioritize the efficiency of irrigation systems. In Andalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Public concern regarding specific environmental issues may fluctuate, contingent on the level of governmental attention and the efficacy of corresponding management strategies (Scott and Willits, 1994). Past studies have identified the association between EC and demographic variables like age, gender, socioeconomic status, residence locations, and political ideology (Liu et al, 2014;Liu and Mu, 2016;Du et al, 2019;Gray et al, 2019;Lafuente et al, 2021). Fu et al (2020) explicated environmental behavioral intention (EBI) as the willingness to engage in pro-environmental activities or behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…Public concern regarding specific environmental issues may fluctuate, contingent on the level of governmental attention and the efficacy of corresponding management strategies (Scott and Willits, 1994). Past studies have identified the association between EC and demographic variables like age, gender, socioeconomic status, residence locations, and political ideology (Liu et al, 2014;Liu and Mu, 2016;Du et al, 2019;Gray et al, 2019;Lafuente et al, 2021). Fu et al (2020) explicated environmental behavioral intention (EBI) as the willingness to engage in pro-environmental activities or behaviors.…”
Section: Introductionmentioning
confidence: 99%